Using Video Tutorials to Improve Students' Scalp and Hair Care Skills - Dewi, Siska Miga; Merita, Yanita (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to determine the effect of using video tutorial media on improving students' skills in performing scalp and hair care. The study used a quasi-experimental method with a one-group pretest-posttest design. The subjects were 32 students of the Make-up and Beauty Study Program who were taking the Scalp and Hair Care course. Data were collected through knowledge tests and practical skills observation sheets, then analyzed using a paired t-test. The results showed an increase in the average score from 62.66 (pretest) to 89.84 (posttest) with a t-value = 13.43 and p < 0.05. Thus, video tutorial media is proven to be effective in improving students' skills in practicing scalp and hair care.